2020
DOI: 10.3390/sym12091401
|View full text |Cite
|
Sign up to set email alerts
|

International Comparative Pilot Study of Spatial Skill Development in Engineering Students through Autonomous Augmented Reality-Based Training

Abstract: Spatial ability is made up of several sub-components, such as the ability to perform mental rotation and object-based transformations. Together with each individual’s attitudes and general skill sets, this specific ability plays an important role in technical professions such as engineering. The components of spatial ability can be enhanced using targeted training or educational programs. This study analyses the levels of spatial skills in first-year engineering students at two universities, one in Spain and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 65 publications
0
23
0
1
Order By: Relevance
“…Further research has demonstrated effective training methods to improve spatial skills in real open environments [30,31]. However, given the rise of emerging technologies such as virtual reality, an increasing body of research is seeking to develop spatial skills in virtual worlds [32,33], in immersive and interactive environments [34], and in virtual navigation experiences [35][36][37].…”
Section: Training Of the Spacial Abilitiesmentioning
confidence: 99%
“…Further research has demonstrated effective training methods to improve spatial skills in real open environments [30,31]. However, given the rise of emerging technologies such as virtual reality, an increasing body of research is seeking to develop spatial skills in virtual worlds [32,33], in immersive and interactive environments [34], and in virtual navigation experiences [35][36][37].…”
Section: Training Of the Spacial Abilitiesmentioning
confidence: 99%
“…Gómez-Tone et al [47], points out that tangible interactions with objects in AR is an added learning value that contributes to improve the understanding of the concept of space. Very similar results have been obtained in the research developed by Bogomolova et al [45] on an application of three-dimensional stereoscopic anatomical models, highlighting the advantages of AR to enhance collaborative and proactive learning.…”
Section: Contributions Of Ar In Stem Content Learning (Rq3)mentioning
confidence: 99%
“…The results of the review also indicate that AR can improve students' motivation, interest and positive attitude towards learning (6 out of 17). These factors have a direct relationship in improving students' academic performance, and in learning both basic and abstract concepts [4,40,43,44,47].…”
Section: Contributions Of Ar In Stem Content Learning (Rq3)mentioning
confidence: 99%
See 1 more Smart Citation
“…As these tests were developed long ago, their original versions exist on paper, however virtual reality (VR) variants were created of them throughout the years, with the only exception being the HSVT [9][10][11][12][13]. Since -according to the literature -, when users are immersed inside a virtual environment (VE), their learning as well as their spatial skills can be enhanced by stimulating cognitive functions [14,15].…”
Section: Introductionmentioning
confidence: 99%